Molecular detection of haemotropic Mycoplasma species in urban and rural cats from Portugal. Issue 6 (June 2015) - Duarte, Ana; Marques, Vânia; Correia, José Henrique Duarte; Neto, Isabel; Bráz, Berta São; Rodrigues, Cláudia; Martins, Telma; Rosado, Ricardo; Ferreira, Joaquim Pedro; Santos-Reis, Margarida; Tavares, Luis
Objectives: The aim of the present study was to evaluate the prevalence of haemoplasma infection in cats in Portugal and to assess risk factors for infection. Methods: Real-time polymerase chain reaction techniques were used to assess 236 urban and rural cats from central and southern Portugal. Results: The overall prevalence of haemoplasma in the target population was 27.1% (64/236), with individual species' prevalences as follows: 17.8% (42/236) ' Candidatus Mycoplasma haemominutum' (CMhm), 14.4% (34/236) Mycoplasma haemofelis (Mhf) and only 5.9% (14/236) ' Candidatus Mycoplasma turicensis' (CMt). Multiple infections were detected in 8.1% (19/236) of the samples, with triple and double infections with Mhf and CMhm being most commonly detected (5.9% [14/236] of cats). Haemoplasma infection was significantly higher in shelter cats ( P = 0.015) than in cats with other lifestyles (eg, free-roaming/house pet/blood donors). Haemoplasma prevalence was also higher in cats with feline immunodeficiency virus infection (FIV; P = 0.011). Although sex was not significantly associated with haemoplasma infection ( P = 0.050), CMt was predominantly found in males ( P = 0.032). Also, the presence of haemoplasma multiple infections was statistically associated with being in a shelter ( P = 0.021), male ( P = 0.057) and with FIV co-infection ( P = 0.004). No evidence of an association between haemoplasma infection and geographical location, age or feline leukaemia virus co-infection was found. Conclusions and relevance: The results obtained in our study are consistent with the documented worldwide prevalence of feline haemoplasma infections, suggesting that the three main feline haemoplasma species are common in Portugal.